Analisis Kelayakan Usaha Industri Rumah Tangga Kerajinan Anyaman Tambir Bambu Di Desa Gondang Rejo Kecamatan Pekalongan Lampung Timur (Studi Kasus Usaha Bapak Sudar) - Lintang Andika Putra; Sugeng; Andiana Rosid (Universitas Muhammadiyah Metro, 2025)
In its existence, small industries often experience ups and downs, there are many problems in its development. This can be based on the factors of natural resources, human resources, production equipment technology, marketing relations, and the lack of small and medium business development. The main problem is in the process of developing a business or maintaining a business. The purpose of this study was to determine the non-financial and financial feasibility conditions of the bamboo tambir woven handicraft household industry in Gondang Rejo Village, Pekalongan District, East Lampung. This research contains an overview of the company and business feasibility in terms of various specific aspects. By choosing the descriptive type because it presented more accurate data, besides that the form was simple, and technically easy to understand. The aspects in question were non-financial aspects and financial aspects. Non-financial aspects in this study included market and marketing aspects, technical and technological aspects, organizational and management aspects, social, economic and cultural aspects, and environmental aspects. While the financial aspects in this study included Net Present Value, Internal Rate of Return, Net Benefit Cost Ratio, and Payback Period. It can be concluded that in the home industry business the bamboo tambir craft was feasible to run. This can be seen from the results of the non-financial aspect analysis, it was found that the business of woven bamboo drums in Gondang Rejo Village was feasible to run. The results of the analysis of the financial aspects of the business feasibility studied show that it was feasible to run. The Village Government must increase its attention to the community in running a business so that it can be more advanced and developed by establishing a special forum for bamboo craftsmen business groups, with the aim of getting the attention of the industry and trade department. The people of Gondang Rejo Village can take advantage of this business opportunity because it is profitable. It will be a loss if you just stand by. In fact, income will not come by itself without doing some effort.